2022
DOI: 10.4103/wjtcm.wjtcm_36_21
|View full text |Cite
|
Sign up to set email alerts
|

Forsythosides as Essential Components of Forsythia-based Traditional Chinese Medicines Used to Treat Inflammatory Diseases and COVID-19

Abstract: The dried fruits of the plant Forsythia suspensa (Forsythia Fructus: Lianqiao in Chinese) are used in many herbal preparations to treat various diseases or the associated symptoms. Forsythia extracts contain phenylethanoid glycosides (PhGs) such as the forsythosides (Fst A-to-P). The leading products, Fst-A,-B and-F (arenarioside), can be found also in >90 other plants inventoried here. The pharmacological properties of Fst are reviewed, with emphasis on their anticancer, antiviral, and antibacterial activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 261 publications
0
7
0
Order By: Relevance
“…In particular, caffeic acid and its derivatives (CAFDs) can be the inhibitors of SARS-CoV-2 and chlorogenic acid as a potential inhibitor for SARS-CoV-2 using molecular docking [42] , [43] , [44] , [45] , [46] . Forsythoside A and forsythoside B are the active constituents from F. suspensa , both of them also showed that activities against the influenza A virus which could be revealed beneficial effects to treat COVID-19 symptom [47] . On the other hand, forsythoside A is a potential anti-COVID-19 active compound of TCM Lianhuaqingwen capsule from China [48] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, caffeic acid and its derivatives (CAFDs) can be the inhibitors of SARS-CoV-2 and chlorogenic acid as a potential inhibitor for SARS-CoV-2 using molecular docking [42] , [43] , [44] , [45] , [46] . Forsythoside A and forsythoside B are the active constituents from F. suspensa , both of them also showed that activities against the influenza A virus which could be revealed beneficial effects to treat COVID-19 symptom [47] . On the other hand, forsythoside A is a potential anti-COVID-19 active compound of TCM Lianhuaqingwen capsule from China [48] .…”
Section: Resultsmentioning
confidence: 99%
“…Caffeic acid and chlorogenic acid also inhibited pro-inflammatory TNF-α and H 2 O 2 -induced IL-8 production [53] . Forsythoside A and B of F. suspensa have been reported that forsythoside A and B inhibited virus-induced inflammatory pathways and viral replication through designated signaling pathways leads to downregulation of several proteins involved in viral infection [54] . For P. frutescen s major compound luteolin could block the interaction of ligands (PAMPs) with the receptors (PRRs) and inhibits downstream activation signals [ [54] , [55] ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forsythiae fructus has a bitter flavor, and has been traditionally applied for thousands of years as an effective remedy for the treatments of carbuncle, scrofula, gall tumor, malignant ulcer, gonorrhea, nephritis, and erysipelas. This medicinal herb is effective in clearing heat channel and releasing the heart of stomach and spleen according to traditional medicine [ 1 , 7 , 8 ]. Recent investigations have shown that Forsythiae fructus has several pharmacological activities such as anti-inflammatory, antibacterial, anti-allergic, anti-cancer, anti-HIV, antioxidant, and neuroprotective activities in vivo and in vitro [ 1 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%